1973
DOI: 10.1677/joe.0.0580405
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake of Testosterone and Zinc in Vitro by the Human Benign Hypertrophic Prostate

Abstract: SUMMARY The uptake of 65Zn and [1,2-3H]testosterone by minced tissue of human benign hypertrophic prostates and the subcellular distribution of radioactivity were examined. The nature of steroid and 65Zn binding by the cytosol (105000 g supernatant) fraction was investigated by gel filtration, ion-exchange chromatography and electrophoresis. It was found that steroid binding after incubation at 4°C was specific. One or two regions of steroid binding were observed after gel filtration of the cytosol using Sepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In seminal plasma much of the zinc was bound to molecules of high and intermediate molecular weight (Table 1). (Reed & Stitch, 1973). Further purification led to the isolation of a histidine-rich zinc-binding protein, whose molecular weight was estimated at 32 000 (Heathcote & Washington, 1973 (Giles & Cousins, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…In seminal plasma much of the zinc was bound to molecules of high and intermediate molecular weight (Table 1). (Reed & Stitch, 1973). Further purification led to the isolation of a histidine-rich zinc-binding protein, whose molecular weight was estimated at 32 000 (Heathcote & Washington, 1973 (Giles & Cousins, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…However, factors such as the cellular distribution and specific protein binding of zinc must be considered rather than the total zinc content of tissue. General ly, nuclear and mitochondrial fractions con tain the highest levels of zinc in prostate [7,13,14], and specific protein binding of zinc appears to be significant [20]. There is vir tually no information regarding the affinity of aconitase for zinc in prostate.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the concentration of zinc between normal and malignant prostatic tissue have also been reported (Schrodt, Hall & Whitmore, 1964;Gyorkey, Min, Huff & Gyorkey, 1967). More recent studies of prostatic subcellular fractions using isotopie zinc have revealed the presence of a zinc-binding protein in this tissue (Reed & Stitch, 1973). Recent reports have suggested that the concentration of free Zn2 + in prostatic cells may influence the further metabolism of testosterone to 5a-dihydrotestosterone (Grant, Min¬ guell, Taylor & Weiss, 1971).…”
Section: Introductionmentioning
confidence: 99%